EXTRACTION AND PURIFICATION OF UNSATURATED FATTY ACIDS FROM HETEROTROPHIC MARINE MICROALGAE SCHIZOCHYTRIUM MANGROVEI PQ6 BIOMASS - Anh, Hoàng Thị Lan (Vietnam Journal of Biotechnology, 2011)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Using a simple and inexpensive procedure involving methylation in dried biomass, urea complexation and winterization in a sequential way, we succeeded in exfracting and purificating of unsaturated fatty acid, especially docosahexaenoic acid (DHA, C22:6n-3) and docosapentaenoic acid (DPA, C22:5n-6) from Schizochytrium mangrovei PQ6 biomass isolated in Phu Quoc island, Kien Giang province on 2006. With the urea/fatty acid ratio was 5:2 at crystallization temperature from 4 to 10°C for 12 hours, total fatty acid was divided into two fractions: non-urea complexing (liquid phase) and urea complexing fraction (solid phase). The non-urea complexing fraction contained a highest amount of DHA and DPA (85.2% and 13.4% total fatty acid of liquid phase, respectively). In the confrast, urea complexing fraction contained mainly saturated fatty acid including palmitic acid more than 55.9% of total fatty acid in this phase. For the reason, this procedure was appropriated for DHA, DPA exfraction and purification from S. mangrovei PQ6 biomas